PERAN BADAN PERMUSYAWARATAN DESA DALAM PEMBUTAN ATURAN PENCEGAHAN COVID-19 DI DESA KALIWEDI KIDUL - Nur Rahman; Harun Fadhli; Sarip Sarip; Urip Giyono; Multahibun Multahibun (Jurnal De Jure Muhammadiyah Cirebon, 2021)
This study has two issues of study in its discussion, the first is a study that is directed to find out and analyze the duties, functions and authorities of the Village Consultative Body (BPD) from the point of view of positive law in Indonesia, and secondly, this study will also discuss how the role and implementation of BPD functions in overcoming and preventing the spread of Covid-19 in their respective villages. This research is a juridical-empirical research that tries to explain the role of BPD in a predetermined research location, namely in Kaliwedi Kidul Village, Kaliwedi District, Cirebon Regency, this study uses primary data as the main data, the primary data as intended by the author is obtained through the data collection techniques used with unstructured observations and interviews, the results of the study show that legally the BPD has a function, namely the legislative function at the village level, the BPD and the village head have an obligation to make a policy in the form of village regulations, however, in Kaliwedi Village, the implementation of this function has not been able to implemented optimally, especially when it is associated with the formation of village regulations concerning the issue of preventing the spread of Covid-19, so it is necessary that in the future BPD can cooperate with village heads, to make policies to overcome Covid-19 in their villages, this is important so that prevention the spread of Covid-19 can have a strong legal basis down to the village level. Keywords: BPD Function, Village Regulation, Covid-19 Prevention